FORMATION OF PEDAGOGICAL CULTURE COMMUNICATION BY DIALOGICAL MEANS LEARNING SITUATIONS (Pedagogy of Higher and Secondary Education, 2022)
The article considers the problem of formation of the Culture of pedagogic Intercourse, reveals the recessity of making up. the dialogue training situations, and shows the positive dynamics of the levels of the culture of pedagogic intercourse.